Factors that Hinder the Return of the IDPs to their Homes at Marawi’s Most Affected Areas - Lumna, Johary B. (RIRAI Publisher, 2024)
ABSTRACT This study is designed to investigate the factors hindering the return of the internally displaced persons (IDPs) in Marawi City resulting from the May 2017 Marawi Siege to the most affected area (MAA), revealing the urgent need for holistic solutions that address property ownership, socio-economic challenges, security concerns, administrative hurdles, and psychological trauma. The primary data required in the study were scientifically obtained through the use of the FGD and key informant interview (KII) methods. More specifically, the study findings disclosed that despite the fact that over 86% of Marawi's displaced longing to return home, a multitude of obstacles stand in their way such as inadequate housing, insecure land ownership, limited livelihoods, lingering trauma, and bureaucratic hurdles create a tangled web of challenges. Moreover, the aforementioned findings were further exacerbated by the exclusion of undocumented residents from reconstruction efforts, widening inequalities and stalling progress. To facilitate a smooth return, comprehensive solutions addressing financial constraints, trauma, community rebuilding, and streamlined administrative processes are critical. Only then can Marawi's displaced rebuild their lives and restore their shattered sense of home. Hence, a comprehensive housing plan offering reconstruction support, flexible payment options, and diverse shelter models for non-owners is crucial; exigent empowerment through financial assistance, skills training, and infrastructure development; addressing psychological well-being through culturally sensitive mental health programs; building trust and accountability requires transparency in resource allocation and addressing concerns about bogus beneficiaries and unauthorized demolitions; and collaboration between government agencies, NGOs, and communities empowers IDPs and ensures their voices are heard.